Cars, trains and planes the definitive visual history of land and air transportation (Dorling Kindersley Penguin Random House, 2016)
Cars, Trains, and Planes chronicles the history of mechanized transportation in awesome detail, profiling the thousands of machines that have carried people around the world over the last two hundred years. This stunning book offers a lavishly illustrated photographic collection of the world's most incredible popular vehicles. Including over 2,500 different machines from the iconic to the unexpected, detailing their specifications and important features. See everything from the first steam engines to the newest high-speed intercity trains; the Model T Ford to the latest hybrid and electric cars; and the Wright Flyer to stealth fighter jets and huge passenger planes. Cars, Trains, and Planes is a celebration of the amazing machines that keep the world on the move.